Engaging rural communities in cancer prevention and control research: Development and preliminary insights from a community‐based research registry. (14th October 2021) - Thomson, Maria D.; Williams, April R.; Sutton, Arnethea L.; Tossas, Katherine Y.; Garrett, Charlotte; Sheppard, Vanessa B.
Abstract: Objective: To report on the development and preliminary findings of a community‐based cancer registry, including the community‐engaged approach to recruitment, participant profile, and distribution of cancer risk factors by race/ethnicity and geography. Methods: Community outreach and engagement best practices were used to recruit a diverse convenience sample of Virginia residents (≥18 years) that oversampled residents living in rural areas, defined as Rural‐Urban Continuum Codes (RUCC) 4–9 and African American (AA)/Black residents. Multiple survey administration methods included electronic (e‐survey) and in‐person survey by community‐based staff. Results: At the time of this analysis, 595 participants are enrolled; 73% are rural, 46% are AA/Black. AA/Black participants reported similar education but lower income ( p  < 0.01) and health literacy ( p  < 0.01), lower alcohol use ( p  < 0.001), fewer sedentary behaviors ( p  = 0.01), but greater BMI ( p  < 0.05) compared to White participants. Rural residents reported significantly lower household income ( p  < 0.001) and greater use of Medicaid ( p  = 0.01) compared to urban participants. Biennial mammography was reported by 82% of women aged 45–74 years old and colonoscopy by 77% of participants ≥50 years old. Tobacco use was reported by 17%; no differences in cancer screening or tobacco use were identified by geography or by race. Conclusion and relevance: Community engagement strategies successfully enrolled diverse residents within the cancer service area. AA/Black participants reported fewer cancer risk behaviors, similar educational attainment but lower income and health literacy compared to White respondents. Nuanced examinations of interactions among multilevel factors are needed to understand how individual, community, and institutional factors converge to maintain cancer disparities among AA/Black Virginians. Additional findings indicate a need for tobacco cessation, lung cancer screening, obesity treatment, and prevention initiatives. Abstract : Community outreach and engagement builds bidirectional relationships among community members, patients, and researchers to prioritize community cancer needs. The Virginia Living Well Research and Registry (VALW) (currently n = 595) was developed to build bidirectional exchange relationships and collect critical longitudinal cancer prevention and control data within the cancer center catchment area.